2015
DOI: 10.1007/s10775-015-9298-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceived influences on the career choices of children and youth: an exploratory study

Abstract: Children's understanding of factors influencing their career choices was examined. Seventy-two children, in grades kindergarten, 4, and 8, responded to questions about their perceptions of career influences. Responses were coded to capture the nature of the influences identified, including the global versus specific and linear versus interacting nature of these influences. Further, influences were coded as existing proximal versus distal to the child. Results indicate that older children identified more career… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
(39 reference statements)
1
20
0
1
Order By: Relevance
“…Counselors could also stimulate middle school children's reflexivity on the role of proximal key figures (e.g., parents) and society on a person's career options, thus promoting a more inclusive and agentic approach to future career decision‐making. This could be done by asking children about perceived influences on their development; fostering children's self‐reflection on the role of key figures and role models in their lives; recommending movies or books that stimulate discussions about a person's role in their community, school, and work contexts; and fostering parent‐child conversations and group discussions about academic and occupational choices, life role management, and the impact of one's behaviors and choices on others and the community (Howard et al, 2015; Kenny et al, 2018; Marques et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counselors could also stimulate middle school children's reflexivity on the role of proximal key figures (e.g., parents) and society on a person's career options, thus promoting a more inclusive and agentic approach to future career decision‐making. This could be done by asking children about perceived influences on their development; fostering children's self‐reflection on the role of key figures and role models in their lives; recommending movies or books that stimulate discussions about a person's role in their community, school, and work contexts; and fostering parent‐child conversations and group discussions about academic and occupational choices, life role management, and the impact of one's behaviors and choices on others and the community (Howard et al, 2015; Kenny et al, 2018; Marques et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, less attention has been devoted to children's expectations. Expectations refer to the education level or job(s) children anticipate attaining based on perceived social influences and their understanding of personal characteristics within contextual affordances (Howard, Flanagan, Castine, & Walsh, 2015; Marques, Silva, Oliveira, Silva, & Taveira, 2017; Rojewski, 2007). Given the need to expand research on children's career expectations and to systematically promote their career development, we examined associations between children's career expectations and parents' jobs in terms of gender, prestige, and interest typology.…”
mentioning
confidence: 99%
“…This can help to prevent the emergence of stereotypical perceptions of certain educational and career paths. Research has shown that early interventions can bring lasting impact on children's development and perceptions of different occupations and of the subjects enabling access to them (see Howard et al 2015 for example for a summary of the evidence arguing the importance of own experiences of children in future career decisions). Gothard (1998) studying children in the United Kingdom finds high levels of interest and engagement amongst primary school (grade 4, 8-9 years) children during 'careers week' and high levels of receptiveness to learning about employment opportunities and skills.…”
Section: Start Early and Continue Into Later Stages In Different Shapesmentioning
confidence: 99%
“…As a result of this, a link between smartphone dependence and relationships with other individuals is generated. With regards to degree title, some authors indicated that the degrees of Social and Infant Education are highly vocational [75][76][77]. This implies a high capacity of attention towards these types of higher studies relative to the degrees of Primary Education and Pedagogy, which are not so specific or vocational.…”
Section: Discussion Of Studymentioning
confidence: 99%